VERB FORMS OF ENGLISH AND SIKKA KROWE LANGUAGE: A CONTRASTIVE ANALYSIS - Sarma Dewi Kemala S; Devi Annisa Marpaung (Dharmas Education Journal (DE_Journal), 2024)
This research was aimed at finding and describing about English and Sikka Krowe language verb forms, the similarities and differences of both language verb forms, the implications of the similarities and differences of English and Sikka Krowe language verbs in teaching English in EFL setting. This research was classified as a qualitative study. The techniques of data collection used in this research were interview and study document. The result of the research showed that both English and Sikka Krowe language verbs changed based on subjects as in English. There are some verbs which do not change in all forms for all times. The difference was that Sikka Krowe language verbs did not have any grammatical tense as in English. Each subject has its own verb form which is used for all times. English have six basic verb forms namely base, to infinitive, present, past, present participle and pas participle whereas Sikka Krowe language only has base forms which different for each subject. Since the difference of both language is caused by the grammatical tense of the verbs, the recommended methods which could be applied are Grammar Translation Method and Community Language Learning